2021
DOI: 10.1158/2643-3230.bcd-21-0012
|View full text |Cite
|
Sign up to set email alerts
|

Monocytic Differentiation and AHR Signaling as Primary Nodes of BET Inhibitor Response in Acute Myeloid Leukemia

Abstract: is a member of Scientific Advisory Boards for Kodikaz Therapeutic Solutions, Coherus Biosciences, and Zenshine Pharmaceuticals, and is an inventor on multiple patients related to CD47 cancer immunotherapy licensed to Gilead.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 83 publications
(1 reference statement)
1
29
0
Order By: Relevance
“…We and others have observed that drug response patterns in AML are sometimes correlated with maturation state of AML tumor cells, with certain drugs exhibiting stronger efficacy against tumors with less differentiated cell state (e.g., BCL2i, cyclin dependent kinase 4/6 [CDK4/6]i; Kuusanmaki et al, 2020;Majumder et al, 2020;Pei et al, 2020;Romine et al, 2021;Zhang et al, 2020) and others showing better efficacy against tumors with more differentiated state (e.g., bromodomain containing 4 [BRD4/BET] i, mitogen-activated protein kinase kinase [MAPKK/MEK]i; Romine et al, 2021;White et al, 2021). Analytical approaches can facilitate the deconvolution of deep-sequencing data to infer proportions of distinct cell types (Avila Cobos et al, 2018), and single-cell sequencing technology has recently defined gene expression patterns for six distinct cell types in AML (hematopoietic stem cell [HSC]-like, progenitor-like, granulocyte-monocyte progenitor [GMP]-like, promonocyte-like, monocyte-like, and conventional dendritic cell [cDC]-like types; Van Galen et al, 2019).…”
Section: Deconvoluting Aml Cell Maturation Statementioning
confidence: 99%
“…We and others have observed that drug response patterns in AML are sometimes correlated with maturation state of AML tumor cells, with certain drugs exhibiting stronger efficacy against tumors with less differentiated cell state (e.g., BCL2i, cyclin dependent kinase 4/6 [CDK4/6]i; Kuusanmaki et al, 2020;Majumder et al, 2020;Pei et al, 2020;Romine et al, 2021;Zhang et al, 2020) and others showing better efficacy against tumors with more differentiated state (e.g., bromodomain containing 4 [BRD4/BET] i, mitogen-activated protein kinase kinase [MAPKK/MEK]i; Romine et al, 2021;White et al, 2021). Analytical approaches can facilitate the deconvolution of deep-sequencing data to infer proportions of distinct cell types (Avila Cobos et al, 2018), and single-cell sequencing technology has recently defined gene expression patterns for six distinct cell types in AML (hematopoietic stem cell [HSC]-like, progenitor-like, granulocyte-monocyte progenitor [GMP]-like, promonocyte-like, monocyte-like, and conventional dendritic cell [cDC]-like types; Van Galen et al, 2019).…”
Section: Deconvoluting Aml Cell Maturation Statementioning
confidence: 99%
“…Since AML remains an incurable disease for the majority of patients, great efforts have focused to develop novel inhibitors during the last decade [ 201 ]. In this sense, CRISPR screening studies have helped to anticipate potential mechanisms of resistance for some of these new therapeutic approaches in AML [ 44 , 73 , 120 , 202 ].…”
Section: Mechanisms Of Drug Resistance Uncovered By Crispr High-throu...mentioning
confidence: 99%
“…Similar approaches have also revealed metabolic genes capable of influencing cellular commitment to apoptosis and sensitizing AML cells to venetoclax [ 82 , 85 ]. Finally, CRISPR high-throughput approaches have anticipated gene determinants to enhance the sensitivity of small molecules under development for AML treatment [ 45 , 73 , 242 ].…”
Section: Hematologic Dependency Map Through Crispr Screens: Essential...mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro CRISPR screens were also utilized to identify genes which sensitizes AML cells to double-negative T cells (DNTs) therapies for effective patient treatments (Soares et al, 2021). Moreover, researchers have also studied the genetic mechanisms that undermine the effectiveness of BCL2 inhibitors in AML treatments using CRISPR-based genome-wide screening (Romine et al, 2021). CRISPR gene knockout screens were also performed to recognize mitochondrial genes necessary for the growth of AML cells.…”
Section: Application Of Various Crispr System In Studying the Functional Genomics Of Amlmentioning
confidence: 99%